Modeling of structure and functions of Antarctic ecosystems with the help of GIS-technologies - Tashyrev, O.B.; Kobzar, L.I.; Usenko, V.P.; Morgun, S.I.; Seredynin, E.S. (Український антарктичний журнал, 2010)
The article presents main approaches to ecosystem modeling with using of GIStechnologies. It was shown that geoinformation systems allow to store, systematize on the spatial principle and analyze information related to biotic and abiotic parameters of ecosystems. Methods of long-termed monitoring of ecosystem structure and functioning, earth surface relief modeling, developing models of ecosystems of lower hierarchical levels were described. Ways of further development of methods for collecting and analyzing data were contemplated. Models of the microorganisms resistance to toxic metals on the biogeographical polygon on island Galindez and models of pigmented forms distribution and a ratio of quantity of pigmented to non-pigmented forms of microorganisms in rock biocoenoses were created. Wide distribution of metal-resistant microorganisms on the biogeographical polygon, their presence in mosses, lichens, sludge, soil and presence of pigmented forms bacteria, micromycetes, yeasts in biocenoses of vertical cliffs were shown. It was shown that usage of GIS-technologies allows to identify the areas, which are the most perspective for searching of producers of biologically active substances. На сегодняшний день комплексное изучение природы Антарктики является приоритетным направлением исследований. Однако моделирование структуры и функций экосистем по-прежнему далеко от завершения и поэтому остается стратегически важным. Оптимальным средством моделирования являются геоинформационные системы. Они позволяют обобщать информацию по пространственному принципу и автоматически включать в комплексный анализ широкий спектр абиотических параметров (высоту над уровнем моря, экспозицию, уклоны и т.д.). Целью работы является усовершенствование методических подходов для систематизации и анализа информации по биотическим и абиотическим параметрам, моделирования антарктических экосистем средствами GIS-технологий. У статті представлено основні підходи до моделювання екосистем за допомогою GIS-технологій. Показано, що геоінформаційні системи дозволяють зберігати, систематизувати за просторовим принципом і аналізувати інформацію, яка стосується біотичних та абіотичних параметрів екосистем. Описано методики моделювання рельєфу земної поверхні, довготривалого моніторінгу структури та функціонування екосистем, створення моделей екосистем нижчих ієрархічних рівнів. Намічено шляхи подальшого розвитку методів збору та аналізу даних. Створено моделі стійкості мікроорганізмів до токсичних металів на біогеографічному полігоні о. Галіндез (Galindez), моделі розподілу пігментованих форм та співвідношення кількості пігментованих і непігментованих мікроорганізмів у скельних біоценозах.